EVALUASI PELAYANAN INFORMASI OBAT TERHADAP KEPUASAN PASIEN DI INSTALASI RAWAT JALAN RSUD DR. MURJANI KABUPATEN KOTAWARINGIN TIMUR PROVINSI KALIMANTAN TENGAH - , Marlia Fatwa, Dra. Siti Munawaroh, Apt, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: the complete drug information service and will support the objective rational treatment. Drug information services can be implemented using standard Depkes and WHO standards. Patients as drug users are entitled to sufficient information about the drugs consumed. Dr hospitals. Murjani as referral hospitals, are required to provide maximum service to consumers. Assessment of quality of service to patients in the form of patient satisfaction surveys can be conducted using servqual which has 2 parts pasien.Pelayanan perceptions and expectations of drug information in pharmacy Hospital Dr. Murjani far using the standard from the Depkes and the evaluation has not been done well against drug information services and patient satisfaction to drug information services. It is therefore necessary to evaluate drug information services based on standards of Depkes and WHO, as well as patient satisfaction with the service drug information. Expected results of this evaluation can help improve the quality of services kefarmasianyang lead to improved service quality drug information and patient satisfaction. Objective: To determine the drug information service on patient satisfaction in outpatient Hospital Dr installation. Murjani Kotawaringin East. Methods of study: This study is a non-experimental study using analytic descriptive research with case study design. The data were analyzed quantitatively and qualitatively. Subjects were patient and pharmacist. The results: the drug information service at hospitals Dr.Murjani generally quite good, although the practice of drug information services to the patients still need to be improved. Measurement of patient care using Depkes indicators showed that the average score is the percentage of drug information services 41%. Measurements with WHO indicator indicates that no drugs are given with the correct label, and the percentage of patients who could repeat the information provided by the officers was 39%. For there is still a gap of patient satisfaction (p <0.05) between the perceptions and expectations of where the gaps are highest in reliability dimension, followed by the dimensions of empathy and last dimension of assurance. Conclusion: drug information services in hospitals Dr.Murjani not in accordance with the Depkes and WHO standards and still there is a significant gap in each dimension of the quality of the analytical results of patient satisfaction.